RISK OF RENEWABLE ENERGY SOURCES DEVELOPMENT IN THE OIL AND GAS INDUSTRY IN THE CONTEXT OF COVID-19 - L. K. Babicheva (Real Economics Publishing House, 2021)
The global climate problem of climate warming has led to the active development of renewable energy almost all over the world. Many European countries and international corporations are already striving for carbon neutrality.This article analyzes the current trends in the development of the renewable energy sources industry in the world and in Russia, assesses the applicability of renewable energy sources in the oil and gas industry and the impact of the coronavirus crisis on the perspectives for renewable energy. The analysis of the indicators of the volumes of commissioning of generating capacities for 2020 is given, the obstacles encountered in the development of the industry due to the unstable global situation are considered.The article also discusses investment in renewable energy by oil and gas companies and their transformation under the influence of the renewable energy sector, as well as the participation of Russian companies in this transformation and their long-term prospects in relation to renewable energy.